2017
DOI: 10.1111/1346-8138.14117
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod 5% cream as a therapeutic option for extramammary Paget's disease

Abstract: A wide local excision is the standard treatment for extramammary Paget's disease (EMPD), though this treatment often leads to permanent anogenital mutilation and functional impairment. The purpose of our study is to evaluate the efficacy and safety of the topical application of imiquimod 5% cream for non-invasive EMPD. We examined nine patients with EMPD. Eight of the nine patients were treated with imiquimod 5% cream three times per week for 16 weeks; one case was treated for 6 weeks. The response rate was 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Skin-directed therapeutic options for sBCC include, among others, cryotherapy, imiquimod (Arits et al, 2013;Geisse et al, 2004), photodynamic treatment, 5-fluoracil (Arits et al, 2013), carbon dioxide laser, and electrocoagulation (Roozeboom et al, 2012). EMPD can benefit from imiquimod (Sanderson et al, 2013;Sawada et al, 2018), photodynamic treatment, 5-fluoracil, carbon dioxide laser, radiotherapy, and topical miltefosine (Asel and Leboeuf, 2019). Skin-directed therapies for MF include topical potent steroids, UVB-and UVA-based light therapies, topical retinoids, bexarotene gel (Breneman et al, 2002;Martin, 2003), 5-fluoracil, ingenol mebutate (Lebas et al, 2017), resiquimod (Rook et al, 2015), topical chemotherapy with carmustine or mechlorethamine, photodynamic treatment, and total body electron beam therapy (Jawed et al, 2014;Lebas et al, 2017;Nguyen and Bohjanen, 2015;Trautinger et al, 2017;Wilcox, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Skin-directed therapeutic options for sBCC include, among others, cryotherapy, imiquimod (Arits et al, 2013;Geisse et al, 2004), photodynamic treatment, 5-fluoracil (Arits et al, 2013), carbon dioxide laser, and electrocoagulation (Roozeboom et al, 2012). EMPD can benefit from imiquimod (Sanderson et al, 2013;Sawada et al, 2018), photodynamic treatment, 5-fluoracil, carbon dioxide laser, radiotherapy, and topical miltefosine (Asel and Leboeuf, 2019). Skin-directed therapies for MF include topical potent steroids, UVB-and UVA-based light therapies, topical retinoids, bexarotene gel (Breneman et al, 2002;Martin, 2003), 5-fluoracil, ingenol mebutate (Lebas et al, 2017), resiquimod (Rook et al, 2015), topical chemotherapy with carmustine or mechlorethamine, photodynamic treatment, and total body electron beam therapy (Jawed et al, 2014;Lebas et al, 2017;Nguyen and Bohjanen, 2015;Trautinger et al, 2017;Wilcox, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study by Sawada et al ., the response rate with imiquimod was 100%, with five of nine patients achieving complete response (complete clinical or histopathological remission). Three of five patients who achieved complete response ultimately recurred, demonstrating the importance of long‐term observation even in cases where complete response is confirmed histopathologically . Despite the benefits of imiquimod, unpleasant local and systemic side effects such as erythema, erosion, fever, and flu‐like symptoms occur in more than 50% .…”
Section: Nonsurgical Interventionsmentioning
confidence: 98%
“…By stimulating the production of multiple cytokines, imiquimod activates the immune system to create an antitumor effect . Multiple studies have reported topical imiquimod 5% cream to be effective for EMPD, with response rates ranging from 52% to 100%, and recurrence rates up to 20% . In a recent prospective study by Sawada et al ., the response rate with imiquimod was 100%, with five of nine patients achieving complete response (complete clinical or histopathological remission).…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%
“…Imiquimod was evaluated by 13 studies (8 cohort studies, 5 case series) in 110 patients. CR was documented in 54% of patients, and 85% achieved clinical regression of 50% or more [43][44][45][46][47][48][49][50][51][52][53][54]60]. Given the propensity of EMPD for recurrence, posttreatment histological evaluation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod is an immune response modifier that stimulates innate immune pathways (via induction of inflammatory cytokines, such as IFN-α, IL-6, and TNF-α) and adaptive immune pathways, resulting in an antitumor effect [59]. Eight cohort studies (3 prospective, 5 retrospective) and 5 case series (total 110 patients) investigated the effectiveness of imiquimod for EMPD at dose schedules ranging from daily to twice weekly for a duration of 2-56 weeks [43][44][45][46][47][48][49][50][51][52][53][54]60]. Overall, 54% (95% CI, 40-67%; I 2 = 37%) of patients achieved complete response (CR) and 85% (95% CI, 74-90%; I 2 = 0%) achieved clinical regression of 50% or more.…”
Section: Imiquimodmentioning
confidence: 99%